Pemodelan Pergerakan Mikroplastik di Selat Bali - I Gede Dananjaya Bagaskara; Yulianto Suteja; I Gede Hendrawan (Fakultas Kelautan dan Perikanan Universitas Udayana, 2020)
The Bali Strait has an important role for the coastal society of East Java and Bali, because as a supplier of lemuru fish. However, the quality of lemuru fish is decrease due to the presence of plastic waste that flow into the Bali Strait. Plastic is a material that’s difficult to decompose, but by using oxidation or mechanical processes causing plastic break to micrometer. Microplastic will be more easily eaten and have a direct impact on the food chain and cause morphological damage or chemical effects that carried by plastic. Based on these problems, its important to conduct research on spatial and temporal microplastic movements in the Bali Strait. However, the wide area of the Bali Strait and the amount of time needed to collect data in the field directly, numerical modeling method was use to solve this problem by using the Finite Volume Ocean Coastal Model (FVCOM) modeled in 3-D and microplastic divided into 3 sizes (0.3 mm, 1 mm, 5 mm). Spatially the movement of microplastic with a size of 0.3 mm, 1 mm, and 5 mm has a relatively similar movement, but has different position based on depth. Temporally the highest total number of microplastic sites is in the potential area of Blimbing Sari catching in the third week, and the potential area for catching Bukit on second week. Whereas in the potential areas of capture Senggrong, Anyir, Watu Anyir and Pang-Pang Bay were not found microplastic.